Discourse Space of the Linguocultural Character Type “Professor” - Sinelnikova, Lara (Respectus philologicus, 2014)
The article offers an analysis of the linguocultural character type professor taking into consideration both traditional set of signs and those transformations that indicate accumulation of evolutionary changes. The methodological base for the systematic description were the achievements of such areas of scientific knowledge as personology, linguopersonology and discourseology. The linguocultural character type (LCCT) is a generalised image of persons, whose behaviour and value orientations influence culture, language and show social originality of the society. The peculiarity of the studied linguocultural character type is in its interrelation with the linguocultural character types intellectual and teacher as well as in the fact of the traditional connection with the concept elite. The exposure of such kind of multidimensional relations allowed to focus attention on the qualities of the LCCT professor that ensure its relative self-sufficiency. The sign of elitism and belonging to the intellectuals of the LCCT professor is asserted by the high social status recognised by the society, which is based on professionalism and compliance with moral principles. The axiological generality of the LCCT professor and teacher is ensured by the peculiarities of the modern pedagogical discourse with its typical image settings. One of the main features of the image of a professor is its belonging to the elite language person. The transformational processes in the contents of the LCCT professor are connected with the globalisation: including the international dimension in the evaluation of the professional activity, complication of the language environment, marketisation of the university sphere.